Observations on leaf color, epiphyll cover, and damage on Malayan Iguanura walliehiana - Kiew, Ruth (International Palm Society, 1982)
lguanura wallichiana (Wall. ex Mart.) Hook.f (formerly known as I. geonomaeformis Mart.) is a common palm throughout the lowlands of Malaya (Kiew 1972a. 1976) growing to about 2 m in height and bearing a crown of about seven to nine leaves. A population of 18 plants of Iguanura wallichiana subsp. malaccensis (Becc.) Kiew in the Gombak Field Station, Selangor was observed over a period of 15 months and the age of leaves derived from weekly measurements of increase in length of the developing apical leaf until expansion and the persistence of the old leaves on the stem (Kiew 1972b). Leaf production is regular and the average interval between leaf production is seven months with a range of S~-10~ months. The time span (plastochrone) between the emergence of the sword leaf (unexpanded leaf) and the expansion of the first leaf (leaf I) was found to be seven months; successive leaves down the trunk are increasingly older by seven months. As shown in Table 1. This species of lguanura has leaves which do not absciss but persist on the trunk until they rot. From the ninth leaf onward the decaying leaves turn pale brown, droop but are still attached to the plant by the very fibrous leaf base. Eventually the lamina falls leaving the persistent leaf base, A few plants have up to 12 leaves in the crown.